Role of Inclusion Size Distribution of Titanium Dioxide on the Nitrogen Oxides Reduction Capability and Microstructural Characteristics of Cementitious Systems - Bahsi, Emrah; Sahin, Oguzhan; Ilcan, Huseyin; Uzal, Burak; Gunal, Muhammed Faruk; Yildirim, Gurkan; Sahmaran, Mustafa (Elsevier Sci Ltd, 2022)
This paper explores the effect of the inclusion size of titanium dioxide (TiO2) particles on a variety of performance properties of cementitious systems via experimental studies. In addition to comprehensive microstructural analysis including pore size distribution and scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX) analyses, particular consideration was given to the effect of particle size distribution (PSD) of TiO2 particles on mechanical and photocatalytic properties and hydration kinetics of cementitious systems. Nano-sized, submicron-sized and micron-sized anatase-phase TiO2 powders were utilized as photocatalysts at a dosage of 5% by total weight of powder material. In addition to the single use of TiO2 particles with three different size ranges (nano, submicron and micron), they were also used in combination by adjusting their PSDs with three different PSD moduli (q): 0.1, 0.5, and 0.9. Test results show that techniques for achieving optimal microstructural characteristics of cementitious systems also help design and improve their performance in favor of multifunctionality. As a result of PSD optimization of TiO2 particles with three different size ranges, which was significantly influential on the microstructure of the cementitious systems, superior photocatalytic degradation results were obtained from mixtures containing lower amounts of nano-sized TiO2 particles. Cementitious composites with denser microstructure showed lower performance in terms of being able to maintain photocatalytic degradation capability for a prolonged period, whereas the opposite was the case for compressive strength.
Ilcan, Huseyin/0000-0002-7853-1907; Sahin, Oguzhan/0000-0003-2104-5761
Keywords: Titanium Dioxide (Tio2); Photocatalytic Activity; Cementitious Systems; Nitrogen Oxides (Nox ) Degradation; Inclusion Size Distribution; Hydration; Titanium Dioxide (TiO2); Nitrogen Oxides (NOx) Degradation